Melhoria da regeneração óssea em ratos diabéticos tipo I submetidos à oxigenoterapia hiperbárica - Linhares, Camila Rodrigues Borges (2019)
Type 1 diabetes mellitus (DM1) is a metabolic disease characterized by hyperglycemia due to changes in insulin secretion and / or action. Chronic hyperglycemia compromises bone metabolism, structure and repair. Adjuvant therapies have been proposed in order to improve structure and bone repair under unfavorable conditions, as occurs in DM1. The aim of the present study was to evaluate the hyperbaric oxygen therapy (HO) effects on bone regeneration in femurs of rats with T1DM. Thirty-two animals were divided into four groups (n = 8): non-diabetic (N); non-diabetic + HO (NH); diabetic (D) and diabetic + HO (DH). In diabetic groups, DM1 was induced by intravenous injection of streptozotocin (50 mg/kg). Thirty days later, bone defect was performed in both femurs and groups with HO were submitted to daily sessions. After 7 days, the animals were euthanized, the femurs were removed, demineralized and embedded in paraffin. The histological sections obtained were stained with Hematoxylin and Eosin (HE) and Mallory Trichrome (MT). In HE, histomorphometric analysis was performed using a 144-point grid to quantify (percentage): bone matrix, blood clot, granulation tissue, and blood vessels. In MT, histomorphometric analysis was performed to quantify the total percentage bone matrix area. Histomorphometric analysis showed that in group D there was more blood clot and granulation tissue, and less blood vessels and bone matrix compared to the other groups. The groups with HO showed less blood clot and granulation tissue, and more blood vessels and bone matrix compared to the groups without HO. The present study showed that hyperbaric oxygen therapy reduces the negative hyperglycemia effects in diabetic rats, improving bone regeneration.